Study of Relationship between Central Venous Pressure and Peripheral Venous Pressure during Intraoperative Period in Neurosurgical Patients - Jay Prakash; Natesh S. Rao; Sanjeev Kumar; Kumar H. Raghwendra; Khushboo Saran; Sandeep D. Reddy (Journal of Neuroanaesthesiology and Critical Care, 2018)
Background and Objectives Central venous pressure (CVP) and peripheral venous pressure (PVP) are strongly correlated during various surgeries. This study was designed to examine the consistency of CVP–PVP relationships in circumstances of rapidly fluctuating hemodynamics in neurosurgical patients. Prime objective of this study was to determine if PVP can be an effective alternative to invasive CVP for assessing volume status during neurosurgical procedures when expertise, equipment, and patient’s condition contraindicate invasive monitoring. Subjects and Methods After the approval by the Institutional Ethics Committee, CVP and PVP were measured in 50 neurosurgical patients of the American Society of Anesthesiologists grade I and II operated in supine position. Paired measurements of CVP and PVP were made every 20 minutes, from the starting of anesthesia until the end of surgery; however, in situations of hemodynamic instability, the readings were taken every 5 minutes of interval. Results The study showed a strong correlation between CVP and PVP (Pearson’s correlation coefficient between CVP and PVP, r = 0.89; 95% CI: 0.81–0.93; p < 0.001). Mean CVP was 5.7 ± 0.8 mm of Hg, mean PVP was 10.4 ± 0.6 mm of Hg, and bias between CVP and PVP was 4.7 ± 0.4 (95% CI: − 4.61 to − 4.83). The Bland–Altman analysis showed that limit of agreement to be 4.0 to 5.5 mm of Hg. Conclusion This study demonstrated a strong correlation between CVP and PVP. Therefore, PVP monitoring may be a reliable alternative to CVP monitoring during neurosurgery.